A thermostable ionic liquid electrolyte for wide-temperature window supercapacitor. (1st December 2022) - Guo, Qiyao; He, Benlin; Tan, Jin; Tang, Qunwei
Abstract: The high-temperature supercapacitors have attracted growing attentions because the improved charge diffusion kinetics and ion conductivity of the electrolytes at elevated temperatures cause high capacitances. However, the state-of-the-art aqueous and/or anhydrous electrolytes always suffer from water or organic solvent evaporation, poor thermal stability and toxicity. We presented here a wide-temperature window supercapacitor made with an activated carbon electrode, a ceramic membrane separator as well as an electrolyte containing 1-methylimidazolium trifluoromethanesulfonate ([MI m ][OTf]) ionic liquid and ethylene glycol (EG) organic solution of potassium hydroxide (KOH) ([MI m ][OTf]/KOH/EG). By studying the impacts of temperature on capacitance, a maximized specific capacitance of 289 F g   −   1 was achieved at 130 °C. Moreover, the champion supercapacitor presented an outstanding charging/discharging stability over 1500 cycles at 130 °C. The high capacitance along with long-term stability suggest that the ionic liquid electrolyte is prospective for wide-temperature window supercapacitors.